PENGARUH PERSEPSI SISWA TENTANG KETELADANAN GURU, MINAT BELAJAR, KESADARAN DIRI, TEMAN SEBAYA, DAN MEDIA SOSIAL TERHADAP KEDISIPLINAN PESERTA DIDIK KELAS X PADA MATA PELAJARAN EKONOMI DI SMA N 1 KOTO BALINGKA KABUPATEN PASAMAN BARAT - Kotmi, Nurhaliza; Citra Ramayani; Lovelly Dwinda Dahen (Global Action and Education for Society, 2026)
This research aims to determine: The influence of Students' Perception of Teacher Role Models, Learning Interest, Self-Awareness, Peers, and Social Media on the Discipline of Class X Students in Economics Subject at SMA N 1 Koto Balingka, Pasaman Barat Regency. This type of research is associative. The population in this study is Class X students in the Economics Subject at SMA N 1 Koto Balingka, Pasaman Barat Regency. The sampling technique used is stratified random sampling based on parental income. The results of this study indicate: there is a significant influence between teacher role models, learning interest, self-awareness, peers, and social media collectively on student discipline with a calculated F value of 327.750 > table F value of 2.34 and a significance value of 0.026 < 0.05.